2014
DOI: 10.1111/aogs.12440
|View full text |Cite
|
Sign up to set email alerts
|

Birth experience of women conceiving with assisted reproduction: a prospective multicenter study

Abstract: ART is not a risk factor for dissatisfaction with childbirth by itself. However, the contributors to an unsatisfactory childbirth differ partly between women conceiving with ART and those conceiving spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Additionally in regard to mean BWs, another study compared singleton donor sperm conceived neonates to all births (including multiples) of spontaneously conceived neonates, 48 which may adversely affect the data as typically multiple births result in lower BWs 55,56 and therefore any effect may be missed. 45 29.3 4.2 years v. unknown Iizuka et al 46 30.1 2.7 years v. unknown Davies et al 47 ( A higher incidence of elective early caesarean section deliveries observed in cohorts of women that have used various forms of ART, 57,58 could also adversely affect outcome measures leading to reduced BWs reported for the donor sperm conceived neonates. These incidences would not be apparent from PD data analysis which is of delivery prior to 37 weeks, as elective caesarean is typically not performed before 37 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally in regard to mean BWs, another study compared singleton donor sperm conceived neonates to all births (including multiples) of spontaneously conceived neonates, 48 which may adversely affect the data as typically multiple births result in lower BWs 55,56 and therefore any effect may be missed. 45 29.3 4.2 years v. unknown Iizuka et al 46 30.1 2.7 years v. unknown Davies et al 47 ( A higher incidence of elective early caesarean section deliveries observed in cohorts of women that have used various forms of ART, 57,58 could also adversely affect outcome measures leading to reduced BWs reported for the donor sperm conceived neonates. These incidences would not be apparent from PD data analysis which is of delivery prior to 37 weeks, as elective caesarean is typically not performed before 37 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…A higher incidence of elective early caesarean section deliveries observed in cohorts of women that have used various forms of ART, 57 , 58 could also adversely affect outcome measures leading to reduced BWs reported for the donor sperm conceived neonates. These incidences would not be apparent from PD data analysis which is of delivery prior to 37 weeks, as elective caesarean is typically not performed before 37 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneously conceived (SC) sample comprised 497 women recruited during their routine ultrasonographic scan in their second trimester. Their randomization was described in detail earlier .…”
Section: Methodsmentioning
confidence: 99%
“…Research on the childbirth experience of formerly infertile women is conflicting. Some studies show that women conceiving with ART have more positive delivery experiences than do women who conceived spontaneously , yet two studies found no difference between ART and women who conceived spontaneously (SC) in their experiences of childbirth. Other studies suggest that, due to delivery complications, women who became pregnant after ART treatment report more negative experiences, such as feeling out of control during the delivery as well as suffering from separation from the baby and postoperative pain .…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-related anxiety, one type of emotional response, has gained attention recently because it has a potential link to preterm birth in the general pregnancy population as well as other poor pregnancy outcomes (Dominguez et al, 2008;Glynn et al, 2008). Moreover, in these mothers with high-level fear of childbirth or severe pregnancyrelated anxiety, an association with dissatisfaction with the actual childbirth process has been recorded (Poikkeus et al, 2014). However, if properly addressed with targeted therapies, the impact on birth outcomes can be affected, including a reduction of cesarean surgeries and increases in satisfaction with birth experience (Rouhe et al, 2013).…”
mentioning
confidence: 99%